Development of Russian-Language Competence of Medical Students (Eurasian Journal of Learning and Academic Teaching, 2023)
Controlling interest in learning the Russian language is one of the main measures to support and promote the Russian language. In the article, the current state of using Russian language teaching methodology in higher educational institutions, in particular, teaching Russian language to students of medical higher educational institutions, developing the culture of communication from a professional and social point of view, intended educational In the literature, the assignment of questions, exercises, and assignments was analytically studied, as well as the works carried out on the improvement of educational and methodical assignments in the following years were referred to. The relevance of the topic is determined by the fact that the problem of methodical provision of the process of teaching professionally oriented speech to students of the medical university has not been developed